Predictors of sleep disturbance in menopausal transition. (December 2016) - Lampio, Laura; Saaresranta, Tarja; Engblom, Janne; Polo, Olli; Polo-Kantola, Päivi
Highlights: Risk factors for menopausal sleep disturbances were seen already in premenopause. These included night sweats, depressive symptoms, the taking of medication for conditions of the central nervous system, personal crises and poor perceived health. Menopause per se appears to have only a minor effect on sleep quality. Hormone therapy provided improved sleep quality. Abstract: Objective: This follow-up study aimed to evaluate risk factors for menopausal sleep disturbances already identifiable before menopause. Methods: At baseline, all 81 women were premenopausal. At year-five follow-up, 27 of the women were premenopausal, 40 postmenopausal, and 14 postmenopausal and using hormone therapy. We used the Basic Nordic Sleep Questionnaire to study sleep; additional questionnaires evaluated risk factors for sleep impairment. Results: Sleep quality differed only marginally between the groups. The following baseline variables were associated with impaired sleep quality at follow-up: depressive symptoms increased the risk of nocturnal awakenings (OR 1.16 (95%CI 1.02–1.32), p  = 0.025), morning tiredness (OR 1.22 (95%CI 1.06–1.40), p  = 0.007), daytime tiredness (OR 1.24 (95%CI 1.06–1.44), p  = 0.007) and propensity to fall asleep during work or leisure time (OR 1.18 (95%CI 1.01–1.37), p  = 0.036). Personal crises increased the risk of longer sleep latency (OR 5.46 (95%CI 1.13–26.32), p  = 0.035) and of propensity to fall asleep when not active (OR 5.41 (95%CI 1.42–20.83), p  = 0.014). Use of medications affecting the CNS increased the risk of worse general sleep quality (OR 11.44 (95% CI 1.07–121.79), p  = 0.044). Perceived impaired general health (OR 2.87 (95%CI 1.04–7.94), p  = 0.043) and frequent night sweats (OR 10.50 (95%CI 2.25–49.01), p  = 0.003) increased the risk of difficulty falling asleep. Conclusions: Various premenopausal health-related factors seem to predict poor sleep in menopausal transition. Menopause itself appears to have only minor effects. Thus, it is essential to identify high-risk women to allow timely interventions that may prevent the development of sleep disturbances at menopause.